Functional Neurosurgery in Africa: A Scoping Review - Nathalie, Ghomsi, Momdjo, Christelle; Sallah, Aminata, Yandeh; Kabulo, Kantenga, Dieu, Merci (My University, 2020)
Functional neurosurgery covers a set of neurosurgical techniques that aims at restoring functional neurologic disorders. In Africa, less data is available to map out this activity, though the increased prevalence of diseases such as epilepsy or Parkinson's disease, which results in a high morbidity and mortality rate. However, functional neurosurgery remains very scarce and costly in these countries, hence difficult to implement. A scoping review will be performed to map functional neurosurgery activities in Africa. The Arksey and O’Malley’s scoping review methodology will be used to collect data, and a PRISMA chart used to follow-up data.
Supplemental Materials: https://osf.io/vzra6/
Keywords: Africa; Functional Neurosurgery